Pemanfaatan Sekam Padi dan Eceng Gondok dalam Memperbaiki Mutu Minyak Jelantah Menggunakan Metode Adsorpsi - Fatunnisa, Lintang; Adzillah, Wilma Nurrul; Suci, Farradina Choria (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2026)
Used cooking oil undergoes a decline in quality due to oxidation and hydrolysis reactions, characterized by an increase in the peroxide value and free fatty acid content. These reactions are triggered by repeated heating at high temperatures (175–180°C), contact with oxygen, and the presence of water from food ingredients during the frying process. This study aims to analyze the effect of the ratio of water hyacinth (Eichhornia crassipes) and rice husk (Oryza sativa L) as adsorbents on the purification of used cooking oil using the adsorption method. The ratio of water hyacinth to rice husk was varied to 100:0, 75:25, 50:50, 25:75, and 0:100, with a used cooking oil volume of 50 mL, an adsorbent dose of 15% (w/v), and a contact time of 120 minutes for each treatment. Water hyacinth was prepared through chemical activation using NaOH, while rice husks were carbonized at 300°C for 2 hours and activated using 10% NaCl. The peroxide value was analyzed using iodometric titration, while free fatty acids were analyzed using alkalimetric titration in accordance with SNI 3741:2013. The results of the study indicate that the ratio of 50:50 provides the most optimal adsorption efficiency, with a reduction in the peroxide value from 18.50 to 5.20 meq O₂/kg and free fatty acids from 1.20% to 0.24%, as well as efficiencies of 71.89% and 80.00%, respectively. The reduction in these parameters was influenced by the interaction between impurities in used cooking oil and the hydroxyl groups on water hyacinth lignocellulose, as well as the silanol groups and pores of rice husk charcoal.